Entwicklungsdiagnostik im Säuglings- und Kleinkindalter - Reuner, Gitta; Pietz, Joachim (Monatsschrift Kinderheilkunde, 2006)
In addition to the diagnostic workup and treatment of diseases, paediatricians today are increasingly confronted with questions concerning infant development. As a result, a well defined knowledge of methods to assess infant and toddler development is highly important. Screening tests, such as the frequently implemented Denver Developmental Scale, can detect developmental delays, which, however, can usually also be detected in clinical check-ups. While more detailed information can be provided by standardized developmental tests such as the Bayley Scales of Infant Development or sophisticated neurological procedures, these methods are expensive and require intensive training. The aims of assessment and psychometric characteristics of the test must be considered in the selection of an appropriate procedure. Thus, knowledge from the fields of biology, medicine and psychology form the interdisciplinary basis necessary for an accurate assessment of toddlers and infants.
Gesehen am 21.02.2019